1999
DOI: 10.1097/00006534-199907000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of Peripheral Nerve Autografts and Allografts

Abstract: We investigated the ability of anti-ICAM-1 monoclonal antibodies to reduce endothelial cell damage by assessing microvascular permeability and microcirculatory function during the acute phase of allograft rejection. The composite rat hindlimb-cremaster muscle transplantation model was employed in three experimental groups of 18 animals each. Isograft control transplantations were performed between genetically identical Lewis (LEW, RT11) rats. Allograft transplantations were performed across a major histocompat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 8 publications
0
49
0
Order By: Relevance
“…Reperfusion appeared to occur in an all-or-none pattern consistent with the mechanism of donor vascular network reconnection to recipient vessels. Though this has not been previously studied in orthotopic tracheal grafts, other studies have demonstrated similar mechanics of revascularization as well as time course in avascular grafts such as skin autografts (19,20) and peripheral nerve allografts (21). Interestingly, the transgenic Tie2/β-galactosidase recipients had many cells in the allograft expressing β-galactosidase.…”
Section: Figurementioning
confidence: 74%
“…Reperfusion appeared to occur in an all-or-none pattern consistent with the mechanism of donor vascular network reconnection to recipient vessels. Though this has not been previously studied in orthotopic tracheal grafts, other studies have demonstrated similar mechanics of revascularization as well as time course in avascular grafts such as skin autografts (19,20) and peripheral nerve allografts (21). Interestingly, the transgenic Tie2/β-galactosidase recipients had many cells in the allograft expressing β-galactosidase.…”
Section: Figurementioning
confidence: 74%
“…Regeneration into nerve grafts is similar; however, the graft must be revascularized early to ensure Schwann cell survival, and minimize fibrous tissue replacement. 2,3 Once the axons have traversed the graft they can be supported by the distal nerve segment and ultimately their end organ (i.e., skin, sensory receptor, neuromuscular junction, or muscle spindle). The axons that reach inappropriate targets or no targets are pruned.…”
Section: Peripheral Nerve Regenerationmentioning
confidence: 99%
“…Recipients of stored allografts require lower dosages of CsA immunosuppression compared to fresh allografts. 21 The use of a vascularized allograft offers theoretical advantages: (1) to allow en bloc reconstruction of nerve plexi; (2) to enhance the rate of nerve regeneration and (3) to permit the utilization of larger "trunk" grafts without the problem of central necrosis. 22,23 When this methodology is applied to the nerve allograft, several interesting observations have been made.…”
Section: Peripheral Nerve Allograftingmentioning
confidence: 99%
“…1 Virginia Commonwealth University, Richmond, VA, USA 2 The Buncke Clinic, San Francisco, CA, USA PNA comes in a 2-to 3-mm diameter option, which can be stacked into cables in an analogous fashion to autograft for bridging gaps in large-diameter nerves. However, PNA is also available in diameters up to 4 to 5 mm that can be used as a single graft to bridge a gap in large-diameter nerves, thus eliminating the need for multicable strands.…”
Section: Research-article2016mentioning
confidence: 99%